Semicryptic Diversity around Chaetoceros elegans (Bacillariophyta, Mediophyceae), and the Description of Two New Species - Chen, Xiumei; Chen, Zuoyi; Lundholm, Nina; Teng, Sing Tung; Xu, Xiaojing; Li, Yang (MDPI, 2022)
The globally distributed Chaetoceros elegans belongs to the Chaetoceros lorenzianus (C. lorenzianus) complex and is characterized by having tear-shaped setae poroids. Several strains of C. elegans were established from Chinese coastal waters. The vegetative cells and the resting spores were observed using light and electron microscopy. Phylogenetic analyses of two nuclear ribosomal RNA genes (SSU and the D1–D3 region of LSU) and the internal transcribed spacer (ITS) revealed that the C. elegans strains clustered into three clades, corresponding to different morphotypes. Based on the type material, the delineation of C. elegans was amended, and two new taxa, (Chaetoceros macroelegans) C. macroelegans sp. nov. and (Chaetoceros densoelegans) C.densoelegans sp. nov., were described. The two new taxa are featured by the presence of two types of setae poroids, tear-shaped and round-oval setae poroids, whereas only tear-shaped setae poroids are seen in C. elegans. The setae base is distinct in C. elegans, but absent or short in the two new taxa. In C. macroelegans, the tear-shaped poroids on the intercalary setae are larger and less densely spaced than in the other two species. The round-oval setae poroids are more densely spaced in C.densoelegans than in C. macroelegans, although they have more or less the same size. Resting spores characterize the two new taxa, but are unknown in the amended C. elegans. When comparing the ITS2 secondary structure, two and four compensatory base changes (CBCs) distinguish C. elegans from C. macroelegans and C.densoelegans, respectively. Between the two new taxa, no CBC but five hemi-CBCs (HCBCs) are present. The shape, size and density of the setae poroids, as well as the morphology of the resting spores, are important characteristics for species identification among the presently nine known species within the C. lorenzianus complex. View Full-Text